Gastroprotective Effect of Carrot (Daucus carota L.) Juice in Rat Models - Wong Hui Jiin; Eva M. Hidayat; Kiki A. Lukman (Althea Medical Journal, 2014)
Background: Gastritis has become one of the very common gastrointestinal tract disorders in clinical practice. One of the factors causing gastritis is the prolonged intake of nonsteroidal anti-inflammatory drugs (NSAIDs) which is commonly adopted by people suffering pain. The NSAIDs such as aspirin cause loss of mucosal integrity resulting in gastric mucosa inflamation. Carrot (Daucus carota L.) has long been used as a traditional medicine for various ailments. The presence of flavonoids and carotenoids in carrot is associated with gastroprotective effect.Methods: The present study was undertaken to determine the gastroprotective effect of 4.08 g carrot juice administered by feeding tube on the hydrochloric acid (HCL) concentration in the stomach in aspirin-induced Wistar-strain rats. This was a laboratory experimental study performed at the Pharmacology Laboratory Faculty of Medicine Universitas Padjadjaran, Bandung Indonesia in October 2012. The parameter used HCL Concentration determined by titration method.Results: The result of carrot juice consumption together with aspirin shows a statistically significant reduction in HCL concentration in the stomach (p<0.05). The result was also significant when compared with another medication, Misoprostol.Conclusion: Carrot juice extract possesses gastroprotective effect when consumed with aspirin and thus support the use of carrot as an alternative treatment. [AMJ.2014;1(1):35–9]Keywords: Aspirin, Carrot juice extract, gastroprotective, HCL concentrationEfek Perlindungan Lambung dengan Jus Wortel  (Daucus carota L.) pada TikusLatar belakang: Gastritis merupakan salah satu kelainan pada saluran pencernaan yang sering ditemui. Salah satu penyebab dari gastritis adalah pemakaian nonsteroidal anti-inflammatory drugs (NSAIDs) dalam waktu lama dan biasanya digunakan oleh orang yang menderita sakit. Obat-obatan NSAID seperti aspirin dapat menyebabkan integritas mukosa menghilang dan terjadinya inflamasi pada mukosa lambung. Wortel (Daucus carota L.) merupakan tanaman tradisional yang sudah banyak digunakan untuk berbagai macam penyakit. Flavonoid dan carotenoid yang ada pada wortel memiliki efek perlindungan terhadap lambung.    Metode: Penelitian dilakukan untuk menentukan  efek perlindungan lambung dengan jus wortel pada konsentrasi HCL dalam lambung tikus yang diinduksi dengan aspirin. Penelitian ini merupakan suatu studi eksperimental yang dilakukan di Laboratorium Farmakologi Fakultas Kedokteran Universitas Padjadjaran, Bandung, Indonesia pada bulan Oktober 2012. Parameter yang digunakan adalah konsentrasi HCL yang ditentukan dengan metode titrasi.Hasil: Hasil dari penggunaan jus wortel bersama dengan aspirin menunjukkan penurunan konsentrasi HCL yang signifikan pada lambung (p<0.05). Hasil ini juga signifikan bila dibandingkan dengan medikasi lain yaitu, Misoprostol.Simpulan: Ekstrak jus wortel memiliki efek perlindungan lambung ketika digunakan dengan aspirin dan hal ini mendukung wortel sebagai pengobatan alternatif.Kata kunci: Aspirin, jus wortel, efek perlindungan lambung, konsentrasi HCL DOI: 10.15850/amj.v1n1.295